Seeing through the Car : The Automobile as Cosmopolitical Proposition in The Fifth Element - Lamarre, Thomas (Cinémas)

(untitled) (Cinémas, 2010)
This essay uses The Fifth Element as a case study for an analysis of how cinema experiments with automobiles, while working through different theoretical approaches to the automobile, those of Marcuse, Baudrillard and Virilio, which pose crucial questions about production, consumption, representation, simulation and perception. Ultimately, however, rather than treat cinema as representation or simulation, this essay provides a close reading of the film in terms of a composition of forces that sets up material orientations. Building on Isabelle Stengers, it shows how the car is not a thing or a sign for cinema, but a force of the outside, a proposition that remains autonomous yet answerable within the field of cinematic composition of forces. Transformations in cinema make this shift in emphasis necessary : assessing the politics of cinema must begin to take into account that the technical non-humans have increasingly come to function as cosmopolitical propositions for cinema.